Eight bears : mythic past and imperiled future - Dickie, Gloria (W.W. Norton & Company, 2023)
"Bears have always held a central place in our collective memory, from Indigenous folklore and Greek mythology to nineteenth-century fairytales and the modern toy shop. But as humans and bears come into ever-closer contact, our relationship nears a tipping point. Today, most of the eight remaining bear species are threatened with extinction. Some, such as the panda bear and the polar bear, are icons of the natural world; others, such as the spectacled bear and the sloth bear, are far less known"--